Gender and Walkability: Case Studies in the City of São Paulo - Kronka Mülfarth, Roberta (2024)
Walking plays the role of the primary structuring axis of the landscape. Recent studies highlight the importance of evaluating walkability from a gender perspective. This article addresses this gap, analysing different in the use of space in central areas of São Paulo, through an urban ergonomic evaluation. The results revealed that the presence of women on the sidewalks is related to mixed-use areas and the presence of active facades. It is suggested that urban planning policies consider these specificities to promote gender equity in walkability and improve the quality of life in cities.